1987
DOI: 10.1111/j.1432-1033.1987.tb13526.x
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the activation of bovine pancreatic procarboxypeptidase A by trypsin

Abstract: Unlike the pancreatic endopeptidase zymogens, procarboxypeptidase A is activated very slowly in vitro. The activation proceeds through the removal of about 100 amino acids away from the N-terminus of the chain. The cleavage of the susceptible bond(s) in monomeric and aggregated forms of bovine procarboxypeptidase A by catalytic amounts of trypsin was found to be very fast. However, as in the case of the porcine zymogen, the expression of the carboxypeptidase activity was considerably delayed by the inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Previous studies suggested that chymotrypsin and elastase might activate procarboxypeptidases in the absence of trypsin (16,17,22,24). We found, however, that human elastases and chymotrypsins, other than CTRC, activated proCPA1/ proCPA2 poorly, even after activation with trypsin (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies suggested that chymotrypsin and elastase might activate procarboxypeptidases in the absence of trypsin (16,17,22,24). We found, however, that human elastases and chymotrypsins, other than CTRC, activated proCPA1/ proCPA2 poorly, even after activation with trypsin (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1). Seminal studies on the activation mechanism of bovine, porcine, rat, and human procarboxypeptidases elucidated that activation is initiated by tryptic cleavage at the C terminus of the connecting segment, which destabilizes helix ␣3 and leads to the dissociation of the inhibitory domain (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In the case of proCPA2 and proCPB, trypsin produced a monophasic activation curve, suggesting that trypsin alone was sufficient to cause propeptide dissociation and complete enzyme activation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The oligomeric association is the most common occurrence of pro-CPAs (Yamasaki et al, 1963;Uren & Neurath, 1972;Kobayashi et al, 1978;Oppezzo et al, 1994), and it has been observed that the quaternary structure affects their activation behavior (Puigserver & Desnuelle, 1977;Kobayashi et al, 1981; Puigserver et al, 1986;Chapus et al, 1987). No complex with proteinase precursors has yet been described for the B form.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, an enhanced catalytic ef®ciency of activated chymotrypsin C within the complex with bPCPA is observed as compared with the monomeric form (Puigserver & Desnuelle, 1977), maybe due to a more rigid conformation of the active site of this enzyme when bound to bPCPA. It has been further postulated that the slow rise in CPA activity during activation of its zymogen could be due to the inhibitory action of its pro-segment (San Segundo et al, 1982;Chapus et al, 1987;Vendrell et al, 1990). According to this, after tryptic cleavage of the pro-segment the stability of the oligomeric complex would be weakened, given that the activation segment of PCPA acts as a link between the metalloenzyme moiety and PPE, as shown in the porcine system (Vilanova et al, 1985).…”
Section: Modulation Of the Proteolytic Activation By The Arrangement mentioning
confidence: 95%